“Creciendo entre líneas”: material didáctico para fortalecer prácticas de escritura desde una perspectiva comunicativa y socioemocional (2024)
The graduation project "Creciendo entre Líneas" presents an innovative educational material specifically designed to strengthen writing practices in fifth-grade students by integrating socio-emotional skills development into the learning process. This resource focuses on enhancing cohesion, coherence, and expressive abilities in textual production, enabling students not only to acquire technical writing skills but also to connect with their emotions and personal experiences. Through structured phases that incorporate reflective activities such as cards and emotional journals, the material provides a safe environment that supports comprehensive learning, positioning writing as a tool for self-reflection and empathy.